A Review on Macroinvertebrates’ Physiological Response to Regulated Stream Flow - Sharma, P.; Sharma, S. (Kathmandu University Journal of Science Engineering and Technology, 2013)
Short rainfall, elevated rates of evaporation, exhaustion of underground water levels, and highly inconsistent stream flow regimes have encouraged the construction of big dams and other water-regulating infrastructure development, resulting in the degradation of river ecosystems. These major changes transform and reduce the biological composition of rivers, isolating populations of aquatic life and their habitats within a river. Invertebrates account for roughly 95% of all animals, so it is important to understand their physiological response to various stressors related to changes in flow regime. This review summarizes the ecological impact of dams in river ecosystems, specifically on macroinvertebrates and their physiology, and highlights potential stressors responsible for environmental disruption.